A taphonomic approach to reconstructing Upper Palaeolithic hunter-gatherer fishing strategies. A load of old trout! - Russ, Hannah (University of Bradford, 2013)
In many cases in the past fish bones recovered during archaeological excavations at Upper Palaeolithic sites were often assumed to result from human activity without any consideration for alternate accumulation processes. Many of these assemblages had not been analysed in a scientifically rigorous manner, with some receiving no consideration at all. A review of current evidence and results of new analyses indicate that salmonids (salmon and trout) are the most frequently recorded fish at the European Palaeolithic cave sites. Two potential accumulation agents for fish remains were explored: brown bears (Ursus arctos) and eagle owls (Bubo bubo). Controlled feeding experiments integrated with ecological studies indicate that salmonid remains survive the digestive systems of both species and result in distinctive patterning in assemblage characteristics. Post-depositional taphonomic processes, such as trampling, also produce distinct taphonomic signatures and are an agent of differential inter-species preservation. A thorough consideration of depositional and post-depositional processes of archaeological assemblages in central Italy (Grotta di Pozzo, Maritza, La Punta and Ortucchio) and Spain (El Juyo, Altamira, Salitre, Castillo and Rascaño) shows that the fish remains from these sites result from human activity. The overrepresentation of cranial elements at the Italian sites suggest that fish were processed by removing the head to perhaps smoke or dry before transportation to other locations for consumption. This research lead to improved methods of analysis, and thus enhanced understanding of the role of fishing and fish consumption in Upper Palaeolithic hunter-gatherer societies.